Appendix A: Anthroponyms attested in the written sources of the Urartian kingdom - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
The prosopography of Urartu includes all available data on anthroponyms connected directly or in some way with the Urartian cultural world. The corpus of the names is presented in five chapters and numerated as Appendix A-E. By their structure the chapters mostly resemble The Prosopography of the Neo-Assyrian Empire, while the main discussions on the names’ etymologies are given in the main text. The names are given according to alphabetic order, including in one list both feminine and masculine personal names. When a personal name is referred to, the text is in bold face. Repeated names are given in chronological order, but the numbers in round brackets do not necessarily indicate any successive order for the throne names. Besides, the references to the names in square brackets are given when the name is cited in another Appendix. Transliterations include all writing forms of the names, giving preference to completely preserved forms, if there are none, then to all attestations of the damaged form. The chronology of the Urartian kings is based upon the studies of the author, with references to alternatives. Appendix A includes personal names attested in Urartian cuneiform inscriptions published to date. It presents only assured names, including fully-preserved and legible, but slightly damaged, as well as defective or completely illegible names attested in stone- and rock-cut display inscriptions, on inscribed metal artefacts, on clay tablets and bullae or on any other material written both in Urartian and Akkadian (Neo-Assyrian) by the kings of Nairi and Biainili (Urartu).